INSTRUMEN TES KECERDASAN LOGIKA-MATEMATIKA UNTUK ANAK USIA DINI - DEWI INDRIATI, NYOMAN UTARI (JPUD - Jurnal Pendidikan Usia Dini, 2016)
This study aims to produce an instrument Logical-mathematical intelligence test in early childhood are valid and reliable. This research was conducted in six kindergartens in Jakarta. The method used in this research is the development method adapted from Dick-Carey instructional models and models of development Djaali-Moeljono. There are three main stages in the development of this instrument to obtain instruments finals, namely: (1) Phase Introduction namely: identify problems and conduct studies theories (2) phase of product development, including designing constructs measured variables based on the theory, development dimension, indicators and grains instruments, testing the validity by experts and panels, a revised instrument panel based on expert input and analysis and reliability testing results. (3) Implementation Phase includes: field trials, conducted empirical test, a revision clause instrument, obtaining final instrument and establishing guidelines for administration and scoring. Test instruments resulting from this research is the instruction sheet, item pictures and marking sheet. The tests showed that whole grains have a significant level of <0.05, with the value of reliability coefficient of 0.856. The results showed that the test instrument LogicalMathematical intelligence fit for use.